INCREASING THE GENERAL AND SPECIAL PHYSICAL FITNESS OF FOOTBALL PLAYERS IN EXERCISES - Bekmurod Anorboyev (European Science Publishing, 2024)
This article provides summery of how to improve the general and special physical fitness of players during training.
Keywords: football, sport, activity, success, training, physical quality, positive preparation.